Alpha-particle emission from the deep-inelastic reaction 1354 MeV Ho-165+ Ta-181 - Sobotka, L. G. (1982)
Fil: Sobotka, L. G. Nuclear Science División, Lawrence Berkeley Laboratory, University o f California; Estados Unidos